Synthesis and characterization of interpenetrating polymer network of deproteinized natural rubber grafted styrene and regenerated cellulose - Tran, Thi Tuyet; Vu, Trung Nam; Nguyen, Quynh Vi; Nguyen, Thu Ha; Tran, Thi Thuy; Nguyen, Ngoc Mai (Vietnam Journal of Science and Technology, 2025)
Non-toxic and environmentally friendly modified natural polymers are a topic of great interest to many researchers. In this study, the effect of combining natural rubber (NR) and regenerated cellulose (RC) which overwhelms the conventional composite materials in terms of physical properties and environmental applications was investigated. The deproteinized natural rubber (DPNR) via graft copolymerization of styrene as the continuous phase. The RC was employed as a reinforcing phase or discontinuous phase. The combination of these two polymers will be made by coprecipitating from a mixture of latex and RC with different NR/RC ratios. The properties of the new bio composite materials were investigated by Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD). The morphology was analyzed by scanning electron microscopy (SEM). The enhancement of thermal properties was examined through thermogravimetric analysis (TGA) and differential scanning thermal analysis (DSC). These results showed that the novel structure formation of RC/DPNR-graft-PS exhibited excellent properties, especially the strengthening ability of cellulose for DPNR-graft-PS was elucidated.